2010
DOI: 10.3109/14756360903514164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant properties of diphenylmethane derivative bromophenols including a natural product

Abstract: Bromination of bis(3,4-dimethoxyphenyl)methanone (5) gave four products (6-9) with mono, di, tri, and tetra Br under different conditions. Reduction and demethylation reactions of product 9 with tetra Br were performed, consecutively and a natural product, 5,5'-methylene bis(3,4-dibrombenzene-1,2-diol) (1), was obtained with a 53% yield. Five derivatives, (13-17) (bromophenols), of 1 were also synthesised. The antioxidant and radical scavenging activities of bromophenols 1 and 13-17 were determined by employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 54 publications
1
100
0
5
Order By: Relevance
“…Also, EA and HES have antioxidative effects that attenuated the muscle damage reducing lipid peroxidation levels. Normally, living organisms are protected from the dangerous effects of O 2 À by SOD, which converts O 2 À into H 2 O 2 [68][69][70] . Whereas, during reperfusion of ischemic tissues, these natural defences may not be overcome and H 2 O 2 is converted into OH , this transformation has the capacity to damage a wide range of biomolecules species containing amino acids, membrane proteins and nucleic acids [71][72][73] .…”
Section: Resultsmentioning
confidence: 99%
“…Also, EA and HES have antioxidative effects that attenuated the muscle damage reducing lipid peroxidation levels. Normally, living organisms are protected from the dangerous effects of O 2 À by SOD, which converts O 2 À into H 2 O 2 [68][69][70] . Whereas, during reperfusion of ischemic tissues, these natural defences may not be overcome and H 2 O 2 is converted into OH , this transformation has the capacity to damage a wide range of biomolecules species containing amino acids, membrane proteins and nucleic acids [71][72][73] .…”
Section: Resultsmentioning
confidence: 99%
“…They are naturally present in almost all plant materials, including food products of plant origin. Phenolics are thought to be an integral part of both human and animal diets [35][36][37][38] . The majority of natural antioxidant compounds are phenolics, and the most important groups of natural antioxidants are flavonoids, which include flavanones, flavanols and flavanonols [39][40][41][42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…They were frequently isolated from red algae of the family Rhodomelaceae and had some important biological activities [53][54][55] . It was reported that the bromophenol derivatives coordinate to the active site Zn 2+ and to block the reaction catalysis.…”
Section: Resultsmentioning
confidence: 99%